Pengembangan media pembelajaran bermuatan nilai pendidikan Islam melalui Running Text berbasis media Proshow di MI Rejosari Pringsurat - Zumrotul Fauziyah; Winarno Winarno (At Turots: Jurnal Pendidikan Islam, 2022)
The type of research used in this research is Research and Development (R&D). Research and development or Research and Development (R&D) is a strategy or research method that is powerful enough to improve practice. The population in this study were all class III students at MI Rejosari, Temanggung Regency, totaling 13 MI, however, the researcher only took samples from class III students at MI Rejosari, totaling 20 students. Development of learning media with proshow by running text on learning and understanding of Islamic education media based on proshow media by (a) Conducting preliminary research, (b) Conducting planning (defining abilities, formulating goals, determining materials and learning sequences, (c) Developing media learning by proshow, (d) Material expert test and media expert test, (e) Small-scale initial field test and revision, (f) Large-scale test and final revision, (g) Application in learning Based on the above significance value tcount = 5.709 with Sig. (2-tailed) 0.000. Before looking at the table of t values, it must first be with db = N - 2. Because the number of samples studied was 40 students, then db = 40 - 2 = 38. db value = 38 at a significance level of 5% obtained t-table = 1.345. Because tcount > ttable or 5.709 > 1.345 and Sig.(2-tailed) = 0.000 <0.05 then H0 is rejected and H1 is accepted. So it can be concluded "there is an effect of using media pe Learning contains the values of Islamic education based on pro-show media on learning outcomes at MI Rejosari Pringsurat Temanggung